2005
DOI: 10.1097/01.ju.0000181205.23233.65
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Shed Her2/Neu Protein in Men With Prostate Cancer Correlate With Disease Progression

Abstract: Increased serum Her-2/neu correlates with the presence of metastatic disease and it may indicate an increased risk of death in patients with castrate, metastatic prostate cancer. The detection of serum Her-2/neu is a minimally invasive alternative to tumor sampling for identifying potential candidates for anti-Her-2/neu treatment strategies. Further studies are needed to optimize this assay for application in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…Furthermore, in prostate cancer cell lines, we found that androgen-sensitive LNCaP cells and castration-resistant C4-2 cells also overexpressed this protein (Figure 3). Our findings are consistent with the majority of patient-related reports in literature, [5][6][7][8]10,11 as well as some in vitro and animal model studies. 13,48,49 Furthermore, it has been recently reported that in men with long-term follow-up after HER-2 targeting of prostate cancer K-x Zhang et al radical prostatectomy, HER-2 expression when combined with percentage DNA index can be used clinically for prediction of progression, metastasis and prostate cancerspecific death.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, in prostate cancer cell lines, we found that androgen-sensitive LNCaP cells and castration-resistant C4-2 cells also overexpressed this protein (Figure 3). Our findings are consistent with the majority of patient-related reports in literature, [5][6][7][8]10,11 as well as some in vitro and animal model studies. 13,48,49 Furthermore, it has been recently reported that in men with long-term follow-up after HER-2 targeting of prostate cancer K-x Zhang et al radical prostatectomy, HER-2 expression when combined with percentage DNA index can be used clinically for prediction of progression, metastasis and prostate cancerspecific death.…”
Section: Discussionsupporting
confidence: 93%
“…In prostate cancers, overexpression of HER-2 has been reported to be associated with progression to androgen independence, [5][6][7][8]10,11 although some contradictory results have also been reported. 39,40 To normalize variables such as fixation and staining procedures, which could account for the reported differences, we used a TMA approach where 105 unique prostate tissue cores from 35 patients were immunostained for HER-2 simultaneously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] The serum levels of HER2/neu ECD protein have been found to be elevated in advanced , hormone-resistant prostate cancer. 4 In addition, we found that a high level of pretreatment serum HER2/neu ECD protein is associated with a high risk of biochemical recurrence after endocrine therapy in patients with metastatic prostate cancer. 5 The ECD of the HER2/neu protein can be cleaved from the cell surface by matrix metalloproteases and then released into the blood.…”
Section: Discussionmentioning
confidence: 82%
“…2 The ECD is shed into the blood stream, and clinical research in prostate cancer has shown that elevated serum levels of circulating HER2/neu ECD were correlated with hormone-refractory disease after endocrine therapy. 3,4 Also, our previous study showed that measuring the pretreatment serum level of HER2/neu ECD of patients with metastatic prostate cancer might be useful in predicting biochemical recurrence after endocrine therapy. 5 Meanwhile, several investigations have shown that overexpression of HER2/neu by immunohistochemical study might be a factor for an unfavorable prognosis in patients with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%